(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
SCI not only handicaps the individual in terms of physical disabilities but also psychological and social dimensions. Anxiety, depression, and social stigma added on by loss of emotional resilience result in being isolated and have lowered self-esteem. This study explores the ability of yoga to enhance emotional resilience, rebuild psychological reliability, and reduce the degree of social stigma in SCI patients.